Ultrahigh-luminosity white-light-emitting devices based on edge functionalized graphene quantum dots. (September 2018) - Kim, Dae Hun; Kim, Tae Whan
Abstract: Graphene quantum dots (GQDs) have received considerable attention as excellent candidates for promising applications in multifunctional optoelectronic devices. The synthesis method for GQDs has been investigated in an attempt to find an optimal method for fabricating white GQDs (WGQDs) suitable for use in display systems. However, the emission wavelengths of WGQDs are still not sufficient to cover the range of wavelengths required by lighting sources, and the luminance of the light-emitting devices (LEDs) based on the WGQDs is still lower than that of white LEDs (WLEDs) fabricated utilizing organic molecular phosphors. Here, we report high-luminosity WLEDs based on edge functionalized GQDs (EF-GQDs) formed by using a simple solution method. The white light emission of the EF-GQDs originates from the various energy states between the octadecylamine functional group and the graphitic domain. The maximum luminance and the Commission Internationale de l'Enclairage coordinates for the WLEDs based on EF-GQDs are 464 cd/m 2 and (0.27, 0.29), respectively. The luminosity of 464 cd/m 2 is, to the best of our knowledge, the highest value ever reported for WLEDs based on GQDs. This successful demonstration of efficiency enhancement for WLEDs based on EF-GQDs can improve our understanding of the mechanisms at play in these devices and lead to their promising applications as backlights in flat panel displays and lighting sources. Graphical abstract: fx1 Highlights: The white emission of the EF- GQDs originates from the various energy states during the functional groups. The Commission Internationale de l'Enclairage coordinates for the WLEDs with the EF-GQDs is (0.27, 0.29). Luminance of the WLEDs with the EF-GQDs is 464 cd/m 2 . WLED with the EF-GQDs have the highest luminance among the reported WLEDs based on GQDs.